Tomato fruit blotch virus cytopathology strengthens evolutionary links between plant blunerviruses and insect negeviruses - Elliot Watanabe Kitajima; Erich Yukio Tempel Nakasu; Alice Kazuko Inoue-Nagata; Renato Barbosa Salaroli; Pedro Luis Ramos-González (Scientia Agricola, 2022)
ABSTRACT Tomato fruit blotch virus (ToFBV) is a blunervirus that causes blotches on mature tomato (Solanum lycopersicon L.) fruits in Italy and Australia in 2020, and was newly detected in Brazil. A cytological study on pericarp tissues from the blotched areas of infected fruits collected in Brasília, Brazil, revealed characteristic cell alterations. Small and slender bacilliform particles (ca. 25 nm wide × 100 nm long) were found accumulating in the perinuclear space and the lumen of the endoplasmic reticulum of the epidermis, peri- and mesocarp cells. No viroplasm-like inclusion was observed either in the nuclei or in the cytoplasm. Such cell alterations are reminiscent of those described in cultured mosquito cells infected by negeviruses, an unofficial group of insect viruses. Negeviruses and some other arthropod-borne viruses shared a common ancestor in the RdRp gene with kitavirids, including blunerviruses. Although additional detailed studies are required, we show evidence that ToFBV particles are enveloped and bacilliform, and that such similarity in cytopathology seems to support the evolutionary relationship between plant kitavirids and insect negeviruses.